ChemInform Abstract: New Monoterpenoids from Fruits of Gardenia jasminoides var. radicans. Issue 3 (29th December 2015) - Yu, Shao‐Fu; Huang, Xiao‐Jun; Fu, Shu‐Na; Wu, Chun; Ye, Wen‐Cai; Zhou, Guang‐Xiong
Abstract: The new lactone, cyclopentanepyrone A (I), and the two new monoterpenoids, gardeterpenone A (II) and jasminoside V (III), are isolated along with four known monoterpenoids.